In vitro antibacterial, antifungal, antioxidant and antihemolytic activities of Alpinia galanga - Anupama Sharma Avasthi; Sanjoli Jain; Manisha Bhatnagar; Sabari Ghosal (International Journal of Phytomedicine, 2015)
In the present study, fractions of methanolic extract of A. galanga were investigated for their antibacterial, antifungal and antioxidant potential. The fractions were first subjected to phytochemical analysis followed by evaluation of their antimicrobial potential against multi drug resistant bacteria (MDR) and fungi by agar diffusion assay and Thin Layer Chromatograpgy - Direct bioautography (TLC- DB). The antioxidant potential was measured by 1, 1-diphenyl-2-picrylhydrazyl (DPPH) scavenging potential and Ferric reducing antioxidant power (FRAP) potential. The selected fractions having high antimicrobial and antioxidant activity were further tested for their protective effect in preventing H2O2 induced hemolysis and lipid peroxidation in human red blood cells. The n-Hex fraction of A. galanga inhibited the growth of MDR Escherichia coli, Staphylococcus aureus and Acinetobacter in significant amounts followed by the DCM and EtOAc fractions. All the fractions of A. galanga also demonstrated significant antifungal activity against Fusarium moniliforme and Candida albicans. Similarly, the n-Hex and DCM fractions exhibited high antioxidant potential in terms of DPPH free radical scavenging and high Fe (III) reduction abilities. Maximum inhibition of hemolysis and lipid peroxidation was also observed for the n-Hex fraction followed by the DCM fraction. The strong antibacterial, antifungal, antioxidant and membrane stabilizing activities of n-Hex and DCM fractions of A. galanga have been demonstrated by us in the present study. These results may offer new possibilities in the therapy of pathological conditions related to development of resistance against MDR microbes and generation of free radicals.